EVALUASI KEBIJAKAN PENANGANAN DAUR ULANG SAMPAH DI INDONESIA - zalfa, jumanah alya; Jumanah, JUMANAH; Gian Sumarna; Ega Muhamad Sigit; M. Abdul Rosyid; Rhima Areslia; Tiara Indah Pratiwi (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
.Waste handling and recycling is a crucial issue in efforts to preserve the environment and public health. This research aims to determine the effectiveness of waste handling and recycling policies implemented in various regions. The methodology used includes qualitative and quantitative analysis of data collected from primary and secondary sources, including interviews with stakeholders, community surveys, and insight into policy documents. The research results show that existing policies have succeeded in increasing public awareness and participation in waste recycling. However, there are various challenges that still lie ahead, such as limited infrastructure, lack of continuous education, and financial constraints. Providing adequate facilities and more sophisticated processing technology has proven to be a determining factor in the success of recycling programs. This research recommends increasing regulations, strengthening education programs, developing infrastructure, and greater financial support to support waste handling and recycling policies. Implementation of these suggestions is expected to increase the effectiveness and sustainability of the waste recycling program, as well as provide a significant positive impact on the environment and the quality of life of the community...